Phytoplankton abundance and diversity in mussel farms of Leyte Bay, Leyte, Leyte Philippines in December 2018-March 2019 - Avelino, Dwight A.
Leyte Bay is known for its rich mussel farms. The study aimed to determine the abundance and diversity of phytoplankton in these farms in Leyte Bay, Leyte, Leyte during December 2018 to March 2019. Samples were collected from three sampling stations monthly within this period. For qualitative analysis, 50mL of samples in three replicates were collected using a plankton net (mesh size: 20 um, aperture diameter: 30 cm, length: 1 m). For quantitative analysis, 1 L samples in three replicates were collected using the bucket method. The total suspended solids, nitrates, phosphates, and Chl-a concentrations were found to have mean values of 128.17 mg/L, 0.94 uM, 0.89 uM, and 0.16 ug/L, respectively. A total of 25 genera of phytoplankton was recorded. Diatoms, represented by 23 genera, made larger contribution to the total abundance in the four sampling months. The highest average phytoplankton abundance was recorded during March 2019 [160.92 x 10 (raised to the power of 4) cells/L]. Skeletonema was found in all sampling periods and was recorded the most dominant genera in the months of December 2018 [1.48 x 10 (raised to the power of 4) cells/L] and March 2019 [104.72 x 10 (raised to the power of 4) cells/L]. Pleurosigma was the most dominant in January 2019 [0.85 x 10 (raised to the power of 4) cells/L] while Bacteriastrum dominated during February 2019 [4.31 x 10 (raised to the power of 4) cells/L]. The highest phytoplankton diversity was recorded during the month of January 2019 with a Shannon-Weiner diversity index of 2.20. Results of the study reflect the importance of physico-chemical parameters and their effect on the phytoplankton community structure in Leyte Bay. Phytoplankton community structure may be influenced by the presence of mussel farms in the area.